2000
DOI: 10.7748/ns2000.05.14.33.32.c2831
|View full text |Cite
|
Sign up to set email alerts
|

Making a difference to practice: clinical benchmarking part 2

Abstract: In the second of two articles, the authors explore further the use of clinical practice benchmarking. In particular, practice related to improving nutritional care for patients, caring for patients with mental health needs and safely transferring critically ill patients is examined. The authors conclude by summarising the value of clinical practice benchmarking and how it made a difference to practice in their trust. The first article appeared in Nursing Standard last week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is important that all interested clinical staff are included in the process and that benchmarking activities are practical and easily coordinated within the confines of allocated resources (Ellis 1995). In large organisations, change can take some time, leading to frustration from clinical colleagues who might expect instant results to justify a return on their investment, particularly in regard to time (Ellis et al. 2000a,b).…”
Section: Why Should Clinicians Participate?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that all interested clinical staff are included in the process and that benchmarking activities are practical and easily coordinated within the confines of allocated resources (Ellis 1995). In large organisations, change can take some time, leading to frustration from clinical colleagues who might expect instant results to justify a return on their investment, particularly in regard to time (Ellis et al. 2000a,b).…”
Section: Why Should Clinicians Participate?mentioning
confidence: 99%
“…However, many staff are unfamiliar with the notion of benchmarking and one rarely sees workplace education and training on this topic. Clinician and team commitment with managerial support are required to promote its acceptance as an effective and integral component of health-care delivery (Ellis 2006;Ellis et al 2000b). This article was developed in response to a perceived clinician need for guidance about benchmarking processes, techniques, and agreement.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature identified a wealth of benchmarking activity appropriate to nursing (Ellis 1995, Ellis & Morris 1997, Bland 2000, Ellis et al 2000, Harrison & Devey 2003, Mason & Brady 2003, Burton 2004, Chaboyer et al 2004, Denner 2004, Terry et al 2004, Vuolo 2004. One study concerned a national initiative launched by the English Chief Nursing Officer entitled 'The Essence of Care' (DH 2003).…”
mentioning
confidence: 99%